Using School Meal Report in improving the performance of school children meal at PAUD Bintang Harapan, Tanjung Morawa, North Sumatera - Haripin Togap Sinaga (Jurnal Abdi Masyarakat (JAM), 2023)
At the age of  0 to 6 year is a period of growth acceleration and development. To achieve growth and development maturation, optimal nutrition is needed (Maisuari, 2022). To meet the optimal nutritional for school children needs better food supplies in school meand or breakfast               In this community service activities, the team designed the school meal report book for scoring the performance of school meal.The food report book is a communication media between teaches and parents on children school food. This book contains seven item to measures, namely 1) type of foods, 2) type of nutritent, 3) processing, 4) meal serving, 4) consumption, 5) consumption, 6) drinks and 7) meal box Every day teachers observe meals dan giving scoring. Number of children used meal report book is 60 children from five classes. Each children have one meal report book. The activities of using meal report book is six weeks. Each item of meal performance was scored into three categories;  6, 8 and 10. Example if  types of foods only 1 or 2 types such as rice and fish it is scored 6. If 3- 4 types it is scored 8 and if more than 4 types the scoe is 10After six weeks using the meal report book, there were positive changes in several items of food performance.Among seven items of food performance, the average score of serving and type of drinks (7.0) are lower than other items. In week 2, five among seven items had low score. Only consumption and meal box had higher scores. This trend of scores also happened in week 3 and week 4. In week 5 and 6, only the score of drinks was low (7.5), while other variable had higher scores; types of foods 7.9, servings 7.9, types of nutrient 7.9 and score for consumption was the highest 9.0.Introducing meals report can affect the performance of school meals in processing, serving and nutrient contents